Brave girl: Clara and the Shirtwaist Makers' Strike of 1909 (Balzer + Bray, 2013)
Description Not Provided

Audacity (Tantor Media, Inc., Philomel Books, An Imprint of Penguin Group (USA), 2019)
"A historical fiction novel in verse detailing the life of Clara Lemlich and her struggle for women's labor rights in the early 20th century in New York."--

She persisted: 13 American women who changed the world (She Persisted, ,, 2019)
"A nonfiction picture book compilation of the stories of 13 American women who persisted in overcoming obstacles and changing the world"--Provided by publisher. "Chelsea Clinton introduces tiny feminists, mini activists and little kids who are ready to take on the world to thirteen inspirational women who never took no for an answer, and who always, inevitably and without fail, persisted. Throughout American history, there have always been women who have spoken out for what's right, even when they have to fight to be heard. In early 2017, Senator Elizabeth Warren's refusal to be silenced in the Senate inspired a spontaneous celebration of women who persevered in the face of adversity. In this book, Chelsea Clinton celebrates thirteen American women who helped shape our country through their tenacity, sometimes through speaking out, sometimes by staying seated, sometimes by captivating an audience. They all certainly persisted. She Persisted is for everyone who has ever wanted to speak up but has been told to quiet down, for everyone who has ever tried to reach for the stars but was told to sit down, and for everyone who has ever been made to feel unworthy or unimportant or small. With vivid, compelling art by Alexandra Boiger, this book shows readers that no matter what obstacles may be in their paths, they shouldn't give up on their dreams. Persistence is power. This book features: Harriet Tubman, Helen Keller, Clara Lemlich, Nellie Bly, Virginia Apgar, Maria Tallchief, Claudette Colvin, Ruby Bridges, Margaret Chase Smith, Sally Ride, Florence Griffith Joyner, Oprah Winfrey, Sonia Sotomayor--and one special cameo"--Provided by publisher.
Harriet Tubman , Helen Keller , Clara Lemlich , Nellie Bly , Virginia Apgar , Maria Tallchief , Claudette Colvin , Ruby Bridges , Margaret Chase Smith , Sally Ride , Florence Griffith Joyner , Oprah Winfrey , Sonia Sotomayor.

Girl power (Binge Box, 2021)
Dancing hands: This empowering, lyrical story of a young girl who fled Venezuela and later became known as the Piano Girl shows the journey that led to her playing for Abraham Lincoln. Muslim girls rise: These eloquent biographies introduce young audiences to the diverse and important contributions Muslim women have made and to role models they may never have heard of before. Counting the stars: At one point, the word "computer" referred to the people who used their knowledge, pencils, adding machines and paper to calculate complex equations needed for space travel. As one of these mathematicians at NACA's (later NASA's) Langley laboratory, Katherine Johnson's skills were in high demand and she was trusted by administrators and astronauts alike to be accurate and reliable. Malala: This beautiful biography outlines the events that led to Malala Yousafzai becoming the youngest Nobel Peace Prize winner and her fight for children's education. Brave girl: When Clara arrived in America, she didn't know that young women had to go to work and grow up fast. But that didn't stop Clara. She went to night school and helped her family by sewing in a factory. She never accepted that girls should be treated poorly with low pay, so she led the largest walkout of women workers the country had seen. She learned that everyone deserved a fair chance, to stand and fight for what she wanted, and, most importantly, that she could do anything she put her mind to. The spacesuit: When Ellie, an ordinary woman, is asked to lead a team of seamstresses to design the very first spacesuit, no one believes they can win, but they're determined to try!
Dancing hands / directed by Andy T. Jones ; illustrated by Rafael (2019 : 15 min.) , Muslim girls rise / illustrated by Aaliya Jaleel ; directed by Andy Jones (2019 : 27 min.) , Counting the stars / illustration by Raúl Colón ; director, Andy T. Jones (2019 : 21 min.) , Malala: Activist for girls / illustration by Aurélia Fronty ; director, Andy T. Jones (2017 : 20 min.) , Brave girl / illustrated by Melissa Sweet (2014 : 9 min.) , The spacesuit: How a seamstress helped put man on the moon / director, Andy T. Jones, illustrator, Ariel Landy (2019 : 14 min.).

Clara Lemlich (She persisted, ,, 2021)
"A biography of Clara Lemlich, part of the She Persisted chapter book series"--
Burning to read , New worlds , All fired up , A fire in her mouth , She persisted! , What would Clara do? , How you can persist.

Brave girl: Clara and the shirtwaist makers' strike of 1909 (Read-a-long, ,, 2014)
"When Clara arrived in America, she didn't know that young women had to go to work and grow up fast. But that didn't stop Clara. She went to night school and helped her family by sewing in a factory. She never accepted that girls should be treated poorly with low pay, so she led the largest walkout of women workers the country had seen. She learned that everyone deserved a fair chance, to stand and fight for what she wanted, and, most importantly, that she could do anything she put her mind to." --

She persisted: 13 American women who changed the world (Weston Woods, 2018)
"Profiles the lives of thirteen American women who have left their mark on U.S. history, including Harriet Tubman, Helen Keller, Margaret Chase Smith, and Oprah Winfrey." --
Harriet Tubman , Helen Keller , Clara Lemlich , Nellie Bly , Virginia Apgar , Maria Tallchief , Claudette Colvin , Ruby Bridges , Margaret Chase Smith , Sally Ride , Florence Griffith Joyner , Oprah Winfrey , Sonia Sotomayor.